PENGEMBANGAN PENDIDIKAN NONFORMAL BIMBEL ENGGON SIN_AU_QU DENGAN METODE SOCIOPRENEUR DI ERA PANDEMI - Dyah Puspita Indah Budi Sari Wulan; Nurleila Jum'ati; Hardo Wahyudi; Risca Ayu Rachmania; Lusy Nur Miftachul Jannah; Mochamad Syahrul Gunawan; Haris Priambodo (Asosiasi Sinergi Pengabdi dan Pemberdaya Indonesia (ASPPI), 2021)
The Covid-19 pandemic has an impact on all aspects of people's lives. One of them is the number of fresh graduates of strata 1 graduates who cannot find a job. Beside, spontaneous changes in online learning methods to suppress covid-19 spreading cause to the obstacles for both students and parents in its adaptation. Parents tend to use non-formal tutoring institution or agencies to support the understanding level of materials provided in schools to overcome these obstacles. Bimbel Enggon Sin_Au_Qu is a non-formal education service provider institution coverage of Surabaya, Sidoarjo, Gresik, Malang, Semarang and even Kalimantan to get the impact of online learning by experiencing an increase in demand for tutor services by absorbing the educated workforce. The absorption of educated workforce is based on sociopreneur methods. The problem experienced by management is that tutors are the majority of fresh graduated. Bimbel Enggon Sin_Au_Qu conduct mentoring methods by facilitating tutors to follow online development training, revamping Enggon Sin_Au_Qu management in managing tutors and service users also developing promotional systems to expand marketing. The results achieved as sociopreneurship are: 1) The development of the potential of tutor human resources, 2) The management system becomes well-coordinated 3) Bimbel Enggon Sin_Au_Qu known by the wider community. Thus, Enggon Sin_Au_Qu as a business container that is able to grow the economic potential that can be enjoyed by various parties involved